Practicing and Presenting Social Research - Robinson, Oral; Wilson, Alexander (Open textbook library.)
This open-access textbook is for those who want to write exemplary social research. It provides an extensive outline of each step of the research process: outlining practical tools for conceptualizing its beginnings, generating proposals, getting ethics approval, relaxing from the stresses of research, writing academically, conducting a literature review, drafting a methods section, collecting the right data, formulating the findings, and sharing the results. Woven throughout each chapter are testimonies of other students who have likewise persevered through the research process, relating their obstacles, solutions, and motivations to each stage of the research process to illuminate not only the technical goals of research, but also the emotional maturity that research entails.